Public Value Of the DUKCAPIL SIAP Service Program (Inclusive Population Administration System and Integrated Services) For Vulnerable Communities In Purbalingga Regency - Rifanda Imawan; Indira Arundinasari (International Journal of Social, Economic, and Business, 2026)
Population administration services are a form of public service that plays a crucial role in ensuring the fulfillment of basic community rights. However, in practice, some groups still experience difficulties in accessing these services, particularly vulnerable groups such as people with disabilities and the elderly with limited mobility. Therefore, the Population and Civil Registration Office in Purbalingga Regency presents a service innovation through the DUKCAPIL SIAP Program as an effort to bring services closer to the community through an outreach mechanism. This study aims to analyze the public value generated from the implementation of the DUKCAPIL SIAP Program. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis was carried out through the processes of data reduction, data presentation, and drawing conclusions. The results show that the DUKCAPIL SIAP Program is able to create public value through three main aspects: legitimacy and support, operational capability, and substantial value generated for the community. This program provides economic benefits through free services, social value through inclusive services for people with disabilities and the elderly, and political, educational, and ecological values that encourage public awareness of the importance of population administration. Thus, the DUKCAPIL SIAP Program can be a public service innovation that contributes to improving the accessibility and quality of population administration services for the community.